2020
DOI: 10.12998/wjcc.v8.i21.5070
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and challenges in the treatment of chronic venous leg ulcers

Abstract: Evaluating patients with chronic venous leg ulcers (CVLUs) is essential to find the underlying etiology. The basic tenets in managing CVLUs are to remove the etiological causes, to address systemic and metabolic conditions, to examine the ulcers and artery pulses, and to control wound infection with debridement and eliminating excessive pressure on the wound. The first-line treatments of CVLUs remain wound care, debridement, bed rest with leg elevation, and compression. Evidence to support the efficacy of silv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 96 publications
0
21
0
Order By: Relevance
“…Current literature indicates similar ulcer healing rates between superficial venous surgery and the use of compression. However, with a lesser recurrence rate [27]. Therefore, the effect of superficial venous surgery on ulcer healing cannot be disregarded in the current study.…”
Section: Discussionmentioning
confidence: 96%
“…Current literature indicates similar ulcer healing rates between superficial venous surgery and the use of compression. However, with a lesser recurrence rate [27]. Therefore, the effect of superficial venous surgery on ulcer healing cannot be disregarded in the current study.…”
Section: Discussionmentioning
confidence: 96%
“…The risk of recurrence exists from a long-term perspective, and skin grafts are still widely used as surgical treatment for CVU [26,27]. On the other hand, surgical treatment using the free flap has the disadvantage of requiring microsurgery, although it offers the major advantage of fundamentally resolving venous insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A commonly known fact is that chronic wound tissues have a too low amount of oxygen, and the healing process of hypoxic tissues is disturbed, especially when a transcutaneous oxygen partial pressure (pO2) is lower than 40 mmHg [ 14 , 26 ]. It is suggested that oxygen therapy (OT) increases oxygen delivery to wounds, accelerates their healing, and does not reveal relevant cell damage risk [ 14 , 27 , 28 ].…”
Section: Oxygen Therapymentioning
confidence: 99%
“…Clinical implications under the influence of hyperbaric oxygen therapy, noted in trials, are reduction in the size of the venous leg ulcers, and acceleration of the healing process [ 14 , 27 , 28 , 29 ]. Nevertheless, there is still a need to conduct high-quality, large randomized, future trials to evidence whether HBOT as an adjunct treatment for non-healing venous leg ulcers improves a long-term disease state [ 14 ].…”
Section: Oxygen Therapymentioning
confidence: 99%
See 1 more Smart Citation